Histomorphological Features of Intestinal Atresia and its Clinical Correlation - Subbarayan, Devi (J Clin Diagn Res, 2015)
INTRODUCTION: Intestinal atresia accounts for approximately one third of all cases of neonatal intestinal obstruction. There is controversy regarding pathogenesis of congenital atresia and stenosis of small bowel. Studies regarding clinical manifestations and specific histopathological features of neonatal intestinal atresia are scarce in Indian literature. AIM: To understand the histomorphological features and thus suggest pathophysiology of cases with Intestinal Atresia. MATERIALS AND METHODS: Out of 147 cases, of intestinal obstruction in newborn studied over a period of 5 years, 39 cases of intestinal atresia were found. Their histomorphological details with clinical manifestations were studied. RESULTS: Type II was the commonest type of atresia. Associated anomalies noted were gastroschisis, volvulus, anal stenosis, microcolon, annular pancreas, meconium cyst and duplication cyst. Histological changes observed were ulceration, flattening, abnormal villous configuration, luminal obliteration, narrowing, haemangiomatous proliferation of blood vessels, fibrosis, haemorrhage, calcification, and mesenchymal condensation around the blood vessels. Gangrene and perforation has also noted in some cases. CONCLUSION: An intrauterine intestinal ischemia due to vascular pathology followed by resorption of the bowel is the possible explanation for the development of intestinal atresia.